Does amount of cut vegetal residue on the canopy influence growth and the structural characteristics of marandu palisadegrass? (Bioscience Journal, 2022)
The pasture mowing in late winter removes the old forage, improving the pasture structure in spring and summer. However, the residue after mowing can affect tillering, thus limiting forage production and the structural characteristics of pasture. We hypothesized that the high amount of cut vegetal residues on the plants in late winter causes a decrease in forage production and modifies the structural characteristics of the forage canopy during the spring and summer. The treatments were four cut vegetal residues (0; 2,000; 4,000 and 8,000 t ha-1 of natural material) deposited on Urochloa brizantha cv. Marandu canopy in late winter. After that, the forage production and structure characteristics were evaluated during the spring and summer for two years. The complete randomized block design, with four replications, was used. The defoliation management was characterized by the adoption of pre- and post-cut heights of 25 and 15 cm, respectively. For both years, there was no effect of cut vegetal residue on all the characteristics evaluated. No variable was affected by the interaction cut vegetal residue amount × year of evaluation. The dead leaf blade percentage was greater in year 2 (6.9%) than in year 1 (3.5%). The average values of variables were live leaf blade percentage = 84.2%; live stem percentage = 8.7%; dead stem percentage = 1.9%; number of vegetative tiller = 653 tiller/m2; number of reproductive tiller = 5 tiller m-2. The forage production rate presented an average value of 46 kg/ha/day of dry matter. The cut vegetal residue amount of up to 8,000 t/ha of natural material on the plants in late winter does not affect the forage production or modifies the structural characteristics of marandu palisadegrass during the subsequent spring and summer.